Evaluation of immunoglobulin M (IgM) and IgG rapid cassette test kits for diagnosis of melioidosis in an area of endemicity. - Wuthiekanun, V; Amornchai, P; Chierakul, W; Cheng, A; White, N; Peacock, S; Day, N (2004)
An enzyme-linked immunosorbent assay-based rapid cassette immunoglobulin G (IgG) and IgM immunochromogenic test kit was compared to the indirect hemagglutination test (IHA) for the diagnosis of acute melioidosis in northeastern Thailand. Admission sera from 70 culture-confirmed septicemic melioidosis patients and 30 patients with localized infections were tested. As a control group, 80 patients with other acute febrile illnesses (other bacterial infections, leptospirosis, or scrub typhus) and 119 healthy individuals were tested. The diagnostic sensitivity of the IgG and IgM tests and the IHA test were 79, 67, and 72%, respectively, with corresponding specificities of 90, 80, and 68%. This kit represents an improvement over IHA for the diagnosis of melioidosis an area of endemicity although, as with other serological tests, it has reduced diagnostic utility in a population with high background seropositivity.